Antibiotic Choice in Laryngectomy Affects Outcomes and Costs: An Analysis of University HealthSystem Consortium Data. (2nd September 2014) - Langerman, Alexander; Pisano, Jennifer; Ham, Sandra
Abstract : Objectives: (1) Identify antibiotic practice patterns for laryngectomy. (2) Determine the clinical and cost outcomes associated with antibiotic management strategies. Methods: University HealthSystem Consortium inpatient billing data on patients undergoing laryngectomy in 2008 to 2011 for 95 academic and affiliated medical centers were analyzed for antibiotic use, outcomes, and cost. Results: Data from 1912 patients (18.1% women) were included in the study. Antibiotic management over the first 72 hours revealed 458 unique management strategies. Antibiotic choice had a significant association with rate of surgical site infection (SSI), with standard regimens of ampicillin/sulbactam (1.4%) or cefazolin+metronidazole (4.3%) having lower rates compared to clindamycin (11.8%; P <. 0001). Non–penicillin‐allergic patients treated with nonstandard regimens had a higher likelihood of wound dehiscence (odds ratio = 2.8 [1.7‐4.5]). Flap procedures on the day of surgery did not have an association with SSI or wound dehiscence in adjusted models. The total cost of hospital admission for patients who were managed with either ampicillin/sulbactam or cefazolin+metronizadole was substantially less than for patients managed with clindamycin ($30, 120 [$28, 807‐$31, 432] versus $37, 164 [$33319‐$41009]; P =. 0007). Conclusions: There is substantial variability in perioperative antibiotic strategies for laryngectomy. Clindamycin had a much higher rate of SSI compared with other common regimens and was associated with a higher total hospital cost. Based on this data, standardization of antibiotic practices should be considered and clinical trials should be planned to firmly establish the most cost‐effective antibiotic management for laryngectomy and determine potential alternatives to clindamycin for penicillin‐allergic patients.